P Pendidikan Kesehatan Berbasis Health Belief Models Tentang Tanda Gejala Awal Stroke (Fast): Literatur Riview - Any Zahrotul Widniah (LPPM Universitas Sari Mulia, 2022)
Introduction:Stroke is a important health problem in the world, each year 5.5 million people die from stroke, and 44 million people lost their lives and were disabled. The stroke attack has a golden period, that is, if a stroke patient is treated immediately, disability and death can be avoided. The golden period of stroke is within the first 4 hours after the patient experiences the symptoms of a stroke, the community needs to be given knowledge about the first signs and symptoms of stroke using the FAST method based on the Health Belief Model (HBM). HBM is a theory used in health education and health promotion. Aim: can understand evidence based in the form of literature review on the effects of HBM-based health education on early signs and symptoms of stroke with the FAST method. Methods: The study was conducted by searching journals in the database